Imagery and metaphors: from movement practices to digital and immersive environments - Stergiou, M.; El Raheb, K.; Ioannidis, Y. (Proceedings of the 6th International Conference on Movement and Computing, 2019)
Imagery is a commonly used practice that is applied in areas such as sports, rehabilitation, therapy and dance. Especially in dance, students of all ages are encouraged by their teachers to use imagery to improve their performance or clearly understand the form and quality of a movement. Mental imagery aims to stimulate thinking with the body, mostly with metaphoric pictures, that usually trigger the sense of sight. These visual or kinaestetic images may include handling imaginary objects, imagining being in particular environments and many other possible imaginary bodily states and shapes. Nowadays motion sensing, augmented and virtual reality technologies offer powerful tools for implementing interactive and real-time visualizations, merging the two worlds of mental imagery and immersive technology into a new range of opportunities. In this work, we raise the question of how design and transition of certain types of imagery into digital experiences might assist dance training. Within an embodied interactive experience, through visual or other modalities, a mental imagery metaphor can be transformed into a visual or other kind of representation consisting an effective and/or creative feedback. In this work, first, we examine the existing imagery approaches in movement practices and we discuss their characteristics. Secondly, we study the existing applications that are proposed by researchers in the field of interactive dance and categorize them in terms of the modalities that they use and the type of metaphors that they are related to. Based on existing literature on augmented performances and reported metaphors, we propose a practical map for implementing self practice tools, reflection tools and learning environments.